What Drives the Sovereign-Bank Nexus? - Isabel Schnabel; Ulrich Schüwer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
The positive relationship between bank and sovereign credit risk in the Eurozone is seen as a major threat for the stability of the Eurozone. This paper explores potential bank-level and country-level drivers of this relationship. We find that banks' home bias in their sovereign exposures and their low equity ratios as well as countries' high debt-to-GDP ratios and low perceived government effectiveness are positively related to the sovereign-bank nexus.
Keywords: G21; G28; 330